Ventriculoperitonealshunt, Programmable or non-programmable - Zamil, Kadhim Hasan; Sapheeh, Raad Sachit (AL-Kindy College Medical Journal, 2014)
Background:Hydrocephalus is dilatation of the ventricular system due to excessive production and/ or obstruction of cerebrospinal fluid (CSF) pathways. Different surgical procedure are used to treat this disease. Ventriculo peritoneal shunt is by far the most popular technique for CSF diversion..Objective;To compare the programmable and non-programmable valves regarding the complications of both typesMethods:This study was conducted in the Neurosurgical hospital of Baghdad/Iraq over a period of 3 years from July 2008 to August 2011.A special inclusion criteria has been tabulated for the selection of patients..Results:.Fifty cases with hydrocephalus admitted and diagnosed by CT scan and treated by ventriculoperitoneal shunts (Codman type).There were 11 cases with programmable valves that demanded revision and 6 patients with fixed pressure valves required revision.Conclusions:The programmable shunt had lower complication rate in adults and it should be used cautiously in infants because of the higher complication rates.